Intellectual Science and Mathematics Program (I-SMP)- enhancing students’ learning interest for better performance / Nurul Akmal Md Nasir … [et al.] - Md Nasir, Nurul Akmal; Mat Salleh, Muhamad Furkan; Mohd Rasid, Nor Syazwani; Abdullah, Nabilah; Ismail, Mohamad Hisyam (Research Innovation Business Unit, 2014)
Substantial discontinuities between what young people experience in their science and mathematics school lessons and in the rest of their lives are commonly observed situation in many countries. Even though students spend about two-thirds of their waking lives outside formal schooling, science and mathematics educators tend to ignore the crucial influences that experiences outside school have on students’ beliefs, attitudes, and motivations to learn. As this problems persist, the declining student performance in science and mathematics and students opting out to non science and mathematics courses are no longer foreign. Lack of motivation to study science and mathematics because poor self perceptions of their ability and strong disconnect between school experiences and the nature of the learning environment are the reasons reported for the unacceptable performance in science and mathematics among students in Malaysia and other countries (Bauer, 2002; Howell, 1999.). Reiss (2000) mentioned that students will only benefit from science and mathematics education when students believe that the knowledge that is being taught is of personal worth to them In this senses, it is imperative that strategies should be designed or developed to address this problem. Research suggests that the use of fun games or activities is an effective means of improving students’ attention, attitudes, and engagement towards learning science and mathematics (Ke, 2008; Squire, 2005; Young-Loveridge, 2005). The appropriately designed tasks or activities will help to focus science and mathematics instruction on conceptual understanding and problem solving which differ from the common instructions employ in the normal classroom. Eventually, it helps to strengthen the connection between the knowledge that the students gained in normal setting and its applications in their daily experiences (Bragg, 2007; McGivern et al., 2007). i-SMP is a special Science and Mathematics program designed for primary and secondary school students to learn science and mathematics in such a way that could cultivate their interest towards science and mathematics as well as to help them to improve the knowledge they learned in science and mathematics class. The activities designed are derived from the content covered in the science and mathematics school curriculum and give focus on strengthening students’ understanding in more fun and enjoyable way. This program also emphasizes the applications of science and mathematics in which, students will be exposed to learning experience that require them to participate in hands-on activities that acquire integration and application of their prior knowledge. This ‘out of classroom learning’ is an avenue to foster meaningful learning that could help students to exploit science and mathematics in a more depth and challenging manner. Hayes (2005) suggested that a good teaching and learning activity should compose of three parts: 1) instruction (what to do); 2) facilitation (how to do it); 3) transcendence (why do it; i.e., its meaning/relevance) and this program was designed based on those three aspects suggested and arranged in specific themes that could benefit the students. By using ‘Fun with Math, Enjoy with Science’ as motto, this program developed by the facilitators and lectures from Science and Mathematics Department, Faculty of Education, UiTM should be able to bring Science and Mathematics learning to a different level and at the same time address the underpinning problems in learning science and mathematics in schools.